Analisis pemanfaatan sewa Barang Milik Daerah dalam meningkatkan Pendapatan Asli Daerah di Kota Tomohon - Pangkey, Gamely Ivanka Alfito Nada; Pangerapan, ⁠Sonny; Poputra, Agus Tony (Yayasan Widyantara Nawasena Raharja, 2025)
This study aims to analyze the utilization of Regional Property (BMD) rental in increasing Regional Original Income (PAD) in Tomohon City. The research employed a descriptive qualitative method, with data collected through in-depth interviews and documentation from the Regional Financial and Revenue Management Agency (BPKPD) of Tomohon City. The findings indicate that the BMD rental mechanism has complied with Ministry of Home Affairs Regulation No. 19 of 2016 and its amendment through Regulation No. 7 of 2024, covering stages such as application submission, feasibility assessment, fair value appraisal, and final approval by the m, ayor. Although the contribution of BMD rental to PAD remains relatively small, it showed a significant increase in 2023, reaching IDR 529.31 million—more than 20 times higher than in 2022. The main challenges include limited asset inventory, irregular revaluation, and weak promotion strategies for asset utilization. These findings imply that optimizing BMD rentals through strengthened administrative procedures, market-based valuation, and enhanced managerial capacity can serve as an effective strategy to increase regional revenue.